Apex predators : [book with audioplayer] the world's deadliest hunters, past and present - Jenkins, Steve, 1952-2021 ([Library Ideas, LLC], 2023)
"In his latest illustrated exploration of the animal kingdom, Steve Jenkins introduces readers to some of the most powerful predators in history, from the Tyrannosaurus rex to the African lion."--